2008
DOI: 10.1124/jpet.108.141309
|View full text |Cite
|
Sign up to set email alerts
|

The Extensive Nitration of Neurofilament Light Chain in the Hippocampus Is Associated with the Cognitive Impairment Induced by Amyloid β in Mice

Abstract: Tyrosine nitration of proteins at an extensive level is widely associated with the cognitive pathology induced by amyloid ␤ peptide (A␤). However, the precise identity and explicit consequences of protein nitration have scarcely been addressed. In this study, we examined the detectable nitration of proteins in the hippocampus of mice with cognitive impairment (day 5) induced by the i.c.v. injection of A␤ 25-35 (day 0). The intensity of the nitration of proteins was inversely associated with the level of recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…At 1 week after injection, A␤ [25][26][27][28][29][30][31][32][33][34][35] induced significant oxidative stress in the hippocampus, as reflected by measured increases in lipid peroxidation, protein nitration, and superoxide generation. [11][12][13]40 In the present study, the early increases in lipid peroxidation levels observed after peptide injection were gradually reduced, particularly in the rat frontal cortex and amygdala, suggesting that oxidative stress could be alleviated by endogenous protective systems (putatively neurotrophins, such as BDNF).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…At 1 week after injection, A␤ [25][26][27][28][29][30][31][32][33][34][35] induced significant oxidative stress in the hippocampus, as reflected by measured increases in lipid peroxidation, protein nitration, and superoxide generation. [11][12][13]40 In the present study, the early increases in lipid peroxidation levels observed after peptide injection were gradually reduced, particularly in the rat frontal cortex and amygdala, suggesting that oxidative stress could be alleviated by endogenous protective systems (putatively neurotrophins, such as BDNF).…”
Section: Discussionsupporting
confidence: 51%
“…brillary tangles (A␤ 25/26 -35 ) and in the degenerating hippocampal CA1 neurons with intracellular neurofibrillary tangles (A␤ [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ), in AD brains, but not in agematched control subjects. 15 Deposits of A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide after its injection have not yet been characterized by IHC, for lack of specific and selective antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides were then administered by intracerebroventricular (i.c.v.) injection as described previously [37][38][39][40][41].…”
Section: Treatment and Experimental Designmentioning
confidence: 99%
“…The reverse peptide, Aβ (Bachem) was prepared in the same way and used as a control. Both peptide stock solutions were incubated at 37°C for 4 days, to allow aggregation prior to administration [37]. The peptides were then administered by intracerebroventricular (i.c.v.)…”
Section: Treatment and Experimental Designmentioning
confidence: 99%
“…In addition, tyrosine nitration contributes to Aβ-induced, and oxidative damage-mediated, cognitive dysfunction in rats and mice [2932]. Recently, we have also demonstrated that tyrosine nitration of hippocampal proteins, specifically neurofilament light chain, correlates with the severity of cognitive impairments in mice [29,31]. …”
Section: Introductionmentioning
confidence: 99%